Machine translation - Bhattacharyya, Pushpak (Taylor & Francis, A CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Franck, Chapman and Hall/CRC, 2015)
List of FiguresList of TablesPrefaceAcknowledgmentsAbout the AuthorIntroductionA Feel for a Modern Approach to Machine Translation: Data-Driven MTMT Approaches: Vauquois TriangleUnderstanding Transfer over the Vauquois TriangleUnderstanding Ascending and Descending TransferLanguage Divergence with Illustration between Hindi and EnglishSyntactic DivergenceLexical-Semantic DivergenceThree Major Paradigms of Machine TranslationMT EvaluationAdequacy and FluencyAutomatic Evaluation of MT OutputSummaryFurther ReadingLearning Bilingual Word MappingsA Combinatorial ArgumentNecessary and Sufficient Con.